Pengaruh Model Pembelajaran Role Playing terhadap Keaktifan Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas XI SMA Negeri 1 Sipoholon Tahun Pembelajaran 2024/2025 (International Forum of Researchers and Lecturers, 2025)
The purpose of this research is to determine the significant positive influence of the role-playing learning model on the learning engagement of Christian Religious Education and Character Education among eleventh-grade students at SMA N 1 Sipoholon in the 2024/2025 academic year. The method used in this study is quantitative research, and the type of research is a pre-experimental design in the form of a